Fake news as an informational moral panic: the symbolic deviancy of social media during the 2016 US presidential election. Issue 3 (23rd February 2020) - Carlson, Matt
ABSTRACT: A persistent story about the 2016 US presidential election was the preponderance of fake news stories on social media, and on Facebook in particular, that had no basis in fact but were wholly concocted to quickly amass clicks that could be converted into advertising revenues. This study steps outside of arguments about the spread or efficacy of fake news to instead interrogate its symbolic dimensions and its meaning for both journalism and the larger system of political communication. To conceptualize the role of fake news as a particular symbol, this paper approaches the journalistic condemnation of fake news as an 'informational moral panic.' This concept builds off Cohen's classic formulation of moral panics as public anxiety that a particular social threat will lead to declining standards. The ability to define a phenomenon as an informational moral panic is an exercise in cultural power that ascribes deviancy to particular actors while validating others. In the case of fake news, the anxiety is not so much directed toward a particular group but aimed at the larger transformation of informational spaces made possible by social media. An examination of journalists' responses in the US press during November 2016 reveals four domains of focus ‒ production, platform, subsidy, and consumption – each with its own narratives of blame and remedy. Fake news becomes a particular signifier that condenses broader concerns surrounding the eroding boundaries of traditional journalistic channels, click-driven news, the extension of mediated voices, and the growing role of social media in news distribution.